The Impact of Socialization Patterns on Building Mental and Social Image of Work for Jordanian Youth - Al-Tarawneh, Sabri; Asasfeh, Rami (Dirasat: Human and Social Sciences, 2024)
Objective: This research aims to determine the impact of socialization patterns on Jordanian youth's mental and social image of work. Methods: For this study, a descriptive-analytical methodology was utilized. A questionnaire was developed to gather information from a sample of 2204 individuals, including both young males and females. The sample was selected using a random sampling method, with 957 males and 1247 females included. Results: The study yields several findings, the most significant of which is the additional protection pattern, which ranks first among Jordanian youth. The majority of the sample members believed that higher positions are occupied by certain segments of society; this perception in general has achieved an average level. Young men and women stated that the society frustrates them towards searching for job opportunities, where the social perception of work has achieved an average level. Conclusion: The study asserts the need to intensify the guidance and awareness of the socialization institutions, especially family, by adopting socially balanced patterns in the methods of socialization in order to avoid transforming it into one of the obstacles towards engaging in the labor market.